Analysis of Determining Road Damage Repair Methods Based on Availability of Budget on the Road Segment of East Java Province - Jarwoto, Jarwoto; Wulandari, Esti; Nugroho, Laksono Djoko (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Pavement damage on the Maospati - Magetan - Cemorosewu Road is severe, with issues such as potholes, surface deformation, peeling asphalt layers, and structural deflections due to heavy vehicle loads. These conditions pose significant risks, particularly during the rainy season, leading to hazardous driving conditions. This research aims to analyze the extent of road surface damage and recommend appropriate maintenance solutions using the PKRMS (Provincial/District Road Management System) method and the Bina Marga method. Data were collected through field surveys and official agency reports to assess road conditions. The findings indicate that the overall road condition is relatively good, with low levels of damage. Based on the Bina Marga and PKRMS assessments, routine maintenance is the most suitable repair strategy to prevent further deterioration and enhance road safety. The research underscores the importance of proactive and regular road maintenance planning to ensure long-term road durability. Future research should explore cost optimization strategies and predictive maintenance models to improve infrastructure sustainability.